Explicit Formulas Involving -Euler Numbers and Polynomials - Serkan Araci; Mehmet Acikgoz; Jong Jin Seo (Abstract and Applied Analysis)
We deal with -Euler numbers and -Bernoulli numbers. We derive some interesting relations for -Euler numbers and polynomials by using their generating function and derivative operator. Also, we derive relations between the -Euler numbers and -Bernoulli numbers via the -adic -integral in the -adic integer ring.